Investigating protein adsorption at solid-liquid interfaces towards the development of functional biomaterial coatings - Park, Jae Hyeon (2018)
Surface and interfacial science is an essential field of study in determining the structure-property design parameters of materials. The fundamental knowledge is especially important in modern days whereby many practical applications rely on the compatibility of organic and inorganic substances. Protein adsorption is one of such areas of research that has been considered highly necessary and relevant for various applications, yet much of its details remain under vigorous scrutiny due to its complexity.